Study of Physical Environment Factors on Pneumonia in Indonesia - Nilandita, Widya (International Conference on Sustainable Health Promotion, 2018)
Pneumonia is a pulmonary disease with a high mortality rate caused by viruses, bacteria, and fungi. Pneumonia as the most significant disease causing the death of children and elderly in the world. The World Health Organization (WHO) in 2005 estimated that toddler mortality due to pneumonia in worldwide was around 19% or ranged from 1.6 to 2.2 million, and approximately 70% occurred in developing countries, especially Africa and Southeast Asia. This study aims to examine physical environmental factors using the incidence of toddlers' pneumonia in Indonesia. This study uses the literature review method. Data sources analyze from the literature. Physical environmental factors that influence the rate of pneumonia in Indonesia are temperature, humidity, ventilation, lighting, floor type and type of wall.